Psychometric properties of Spanish-language adult dental fear measures - Heaton Lisa J; Garcia Laura J; Chambers Mark A; Coolidge Trilby; Coldwell Susan E (BMC, 2008)
Abstract Background It would be useful to have psychometrically-sound measures of dental fear for Hispanics, who comprise the largest ethnic minority in the United States. We report on the psychometric properties of Spanish-language versions of two common adult measures of dental fear (Modified Dental Anxiety Scale, MDAS; Dental Fear Survey, DFS), as well as a measure of fear of dental injections (Needle Survey, NS). Methods Spanish versions of the measures were administered to 213 adults attending Hispanic cultural festivals, 31 students (who took the questionnaire twice, for test-retest reliability), and 100 patients at a dental clinic. We also administered the questionnaire to 136 English-speaking adults at the Hispanic festivals and 58 English-speaking students at the same college where we recruited the Spanish-speaking students, to compare the performance of the English and Spanish measures in the same populations. Results The internal reliabilities of the Spanish MDAS ranged from 0.80 to 0.85. Values for the DFS ranged from 0.92 to 0.96, and values for the NS ranged from 0.92 to 0.94. The test-retest reliabilities (intra-class correlations) for the three measures were 0.69, 0.86, and 0.94 for the MDAS, DFS, and NS, respectively. The three measures showed moderate correlations with one another in all three samples, providing evidence for construct validity. Patients with higher scores on the measures were rated as being more anxious during dental procedures. Similar internal reliabilities and correlations were found in the English-version analyses. The test-retest values were also similar in the English students for the DFS and NS; however, the English test-retest value for the MDAS was better than that found in the Spanish students. Conclusion We found evidence for the internal reliability, construct validity, and criterion validity for the Spanish versions of the three measures, and evidence for the test-retest reliability of the Spanish versions of the DFS and NS.